18F-FDG PET-CT Evaluation of Primary Adrenal Ewing Sarcoma with Venous Thrombosis: An Unusual Presentation - Debdip Roy; Melvika Pereira; Divya Shivdasani; Natasha Singh (World Journal of Nuclear Medicine)
Ewing sarcoma (EWS) is primarily an osseous malignancy of childhood and young adults. Extraskeletal occurrence is less frequent and primary adrenal involvement is an even rare presentation. We present such a case of a 7-year-old boy diagnosed with adrenal EWS with associated venous thrombosis and pulmonary embolism detected on 18F-fluorodeoxyglucose positron emission tomography-computed tomography scan.